2014
DOI: 10.1007/s10773-014-2254-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Signature Scheme Using a Single Qubit Rotation Operator

Abstract: We present a quantum signature scheme using a single qubit rotation operator. In this protocol, the trusted center confirms the quantum signature and thus conforms with other quantum signature schemes. Utilizing the unitary properties of a single qubit rotation operator and Pauli operators, our protocol provides signature security and enhances the efficiency of communication. In addition, our protocol -using only a single qubit measurement -facilitates the ease of implementation and enhances convenience for us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Zhang et al, however, showed that the (I, H)-type quantum encryption is not secure for improved Gao's forgery [49,50]. We [19,34] overcome the original Gao's forgery [46] or the improved Gao's forgery [49,50] with quantum encryption σ k i AB H k i H , which randomly uses operator H. Here, the number of all possible cases of quantum encryption…”
Section: Experiments Setup and Measurement Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Zhang et al, however, showed that the (I, H)-type quantum encryption is not secure for improved Gao's forgery [49,50]. We [19,34] overcome the original Gao's forgery [46] or the improved Gao's forgery [49,50] with quantum encryption σ k i AB H k i H , which randomly uses operator H. Here, the number of all possible cases of quantum encryption…”
Section: Experiments Setup and Measurement Resultsmentioning
confidence: 98%
“…Shamir's three pass protocol has the advantage that two parties, e.g., Alice and Bob, can share information without exposing their own private keys. In the implementation, the central idea is that the commutative property [19] of exponential operation in Shamir's three-pass protocol is implemented using single-qubit rotation operators consisting of linear combinations of wave plates. To our knowledge, this is the first time a quantum message authentication protocol has been proposed using the quantum three-pass protocol, though other applications of the quantum three-pass protocol, such as direct communication [32], quantum key distribution [30], and quantum signature [19], have been proposed theoretically.…”
Section: Quantum Message Authentication Protocolmentioning
confidence: 99%
See 3 more Smart Citations